Pelaksanaan Proses Supervisi Kepala Sekolah Di SMK Komputer Karanganyar Kebumen - Pangestuti, Diana Wahyu; Murtopo, Bahrun Ali; Wi Hargina, Devi Yaniar (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
The aims of this study were to determine the process of supervision carried out by the principal at SMK Komputer Karanganyar Kebumen. This research was conducted with 5 respondents, namely the principal and 4 teachers of SMK Komputer Karanganyar Kebumen. the method used in this research is a qualitative research method. The data collected is in the form of supervision data carried out by the Karanganyar Komputer Vocational School, Kebumen. The data analysis used is qualitative data analysis. The data analysis technique used is data reduction, data presentation and conclusion drawing and verification. Based on the results of the study, it can be concluded that there are two kinds of supervision processes in the Karanganyar Komputer Vocational School, Kebumen, namely the supervision of learning planning and supervision of the implementation of learning.